DEGREE OF AGREEMENT BETWEEN ULTRASONOGRAPHY AND MAGNETIC RESONANCE IMAGING FOR DETECTION OF NON-PALPABLE TESTIS AMONG PATIENTS WITH CRYPTORCHIDISM - IQBAL, J; INAM, T; ELAHI, I; TARIQ, MA (Biological and Clinical Sciences Research Journal, 2023)
The current study aimed to determine the degree of agreement between ultrasonography and magnetic resonance imaging to detect non-palpable testis among patients with cryptorchidism. This cross-sectional study was conducted at the Department of Radiology, Jinnah Hospital, Lahore, from 15th May 2014 to 14th November 2014. 120 patients under 12 years of age with cryptorchidism were included to detect the presence or absence of testis by magnetic resonance imaging and ultrasonography. 120 patients had a mean age of 5.10 ± 2.5 years ranging from 2 to 11. 90 patients (75%) showed undescended testes by ultrasonography while MRI detected the presence of undescended testes in 98 patients (81.7%). 84 patients were detected for the presence and 16 for the absence of undescended testes by MRI and ultrasound (kappa = 0.512). It is concluded that the agreement between ultrasonography and magnetic resonance imaging (51.2%) is although moderate yet acceptable for detection of non-palpable testis among patients of cryptorchidism.